Tumour proliferation, angiogenesis, and ploidy status in human colon cancer. Issue 11 (27th October 2005) - Cristi, E; Perrone, G; Toscano, G; Verzì, A; Nori, S; Santini, D; Tonini, G; Vetrani, A; Fabiano, A; Rabitti, C
Abstract : Aims: Tumour angiogenesis is essential for carcinogenesis and facilitates the process of tumour development and metastasis. Vascular endothelial growth factor (VEGF) is a well characterised angiogenetic factor and is known to play a crucial role in new vessel development. To gain further insight into the effects of microvessel density and VEGF expression in colon cancer, their relation with tumour proliferation, ploidy status, and p53 expression was investigated in colon cancer. Methods: Tissue samples of 50 archived colon cancers were analysed by immunohistochemistry for VEGF, p53, and the endothelial cell marker, von Willebrand factor (VWF), using specific antibodies. The same samples were re-cut for flow cytometric studies to obtain S phase fraction (SPF) and ploidy status. Results: A positive significant correlation was found between SPF and angiogenesis. The median microvessel count in high SPF tumours was significantly higher than in low SPF ones. No association was found between VEGF expression and SPF. A positive correlation was found between ploidy status and p53 expression and microvessel count. Furthermore, a positive correlation was established between DNA ploidy, VEGF expression, and microvessel count. Conclusion: This study provides evidence that in colon cancer, tumour growth may be stimulated by vascular supply, and the lack of a correlation between tumour cell proliferation and VEGF expression indicates that these two parameters may be regulated by separate mechanisms. Furthermore, the positive correlation between microvessel density, VEGF expression, and ploidy status provides more evidence that genetic alterations are involved in tumour angiogenesis.